TEORI PENDIDIKAN MORAL MENURUT EMILE DURKHEIM RELEVANSINYA BAGI PENDIDIKAN MORAL ANAK DI INDONESIA - Sinulingga, Setia Paulina (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2016)
Morality is an asset in self development process. Morality has become a universal problem, both in developed or traditional society, since morality damages in a person would disturb another's peace. If there are so many people in society who has damaged morality, the society could be shocked. Morality education for children could change their behavior, thus, when they grow older, they'll become a responsible adult and has respect to the others and capable to meet the challenges of the world that rapidly changing. The increase of moral consideration in children which designed through school education could improve the formation of children personality. With the formation of morality consideration, the child would behave in accordance with his or her way of morality thought. Three elements which suggested by Durkheim to become a person with morality are discipline, group attachment, and autonomy. Each individual should have these three elements to be a morality personality. And morality act, in essential, is a central focus in morality world which form a responsible, discipline personality, as well as a good person in society who avoids bad behavior and act in accordance with given morality thought.